2019
DOI: 10.3390/antibiotics8040206
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin, a Popular Dietary Supplement Shows Anti–Candida Activity

Abstract: Silymarin is a complex of plant-derived compounds obtained from the seed shells of the milk thistle (Silybum marianum). It is used in medicine primarily to protect the liver. The mixture contains mainly flavonolignans, with silybin as a paramount bioactive component of the extract. This article presents the potential health benefits for silymarin as an antifungal drug against five references strains: C. albicans, C. glabrata, C. parapsilosis, C. tropicalis, and C. krusei with MIC (minimum inhibitory concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…With regard to the activity of S. marianum -derived phytochemicals, the antifungal activity of silymarin/silibinin against Candida spp. and its underlying mechanism has been studied by Yun and Lee [ 18 , 61 ] and Janeczko and Kochanowicz [ 62 ]. Fernández, et al [ 63 ] found significant inhibition against Fusarium graminearum Schwabe for four flower defensins from milk thistle.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the activity of S. marianum -derived phytochemicals, the antifungal activity of silymarin/silibinin against Candida spp. and its underlying mechanism has been studied by Yun and Lee [ 18 , 61 ] and Janeczko and Kochanowicz [ 62 ]. Fernández, et al [ 63 ] found significant inhibition against Fusarium graminearum Schwabe for four flower defensins from milk thistle.…”
Section: Discussionmentioning
confidence: 99%
“…Among the fungal pathogens, Candida species not only cause mucosal infections but are also responsible for systemic infection in humans . Silymarin inhibits the growth of Candida albicans, possibly via destruction of the membrane, and reduces its virulence through interference with the destabilization of mature biofilms and secretion of hydrolases. Plasmodium falciparum is the most highly pathogenic human malaria parasite, responsible for high morbidity and mortality worldwide . Silymarin reduces the viability of P.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Data on the antifungal activity of silymarin with 5 reference strains of Candida is known [ 26 ]. Data presented here shows that Silymarin is of potential use in the down regulation of the virulence factors by destabilisation of the mature biofilm by inhibition of hydrolases in the local environment in the context.…”
Section: Resultsmentioning
confidence: 99%